Analysis of the CRISPR-Cas system in bacteriophages active on epidemic strains of Vibrio cholerae in Bangladesh. Issue 1 (December 2017) - Naser, Iftekhar; Hoque, M.; Nahid, M.; Tareq, Tokee; Rocky, M.; Faruque, Shah
Abstract CRISPR-Cas (clustered regularly interspersed short palindromic repeats-CRISPR-associated proteins) are microbial nuclease systems involved in defense against phages. Bacteria also resist phages by hosting phage-inducible chromosomal islands (PICI) which prevent phage reproduction.Vibrio cholerae which causes cholera epidemics, interacts with numerous phages in the environment and in cholera patients. Although CRISPR-Cas systems are usually carried by bacteria and archea, recentlyV .cholerae specific ICP1 phages were found to host a CRISPR-Cas system that inactivates PICI-like elements (PLE) inV .cholerae . We analyzed a collection of phages andV .cholerae isolated during seasonal cholera epidemics in Bangladesh, to study the distribution, and recent evolution of the phage-encoded CRISPR-Cas system. Five distinct but related phages carrying the CRISPR-Cas system, and possible CRISPR-Cas negative progenitor phages were identified. Furthermore, CRISPR arrays in the phages were found to have evolved by acquisition of new spacers targeting diverse regions of PLEs carried by theV .cholerae strains, enabling the phages to efficiently grow on PLE positive strains. Our results demonstrate a continuing arms-race involving genetic determinants of phage-resistance inV .cholerae, and the phage-encoded CRISPR-Cas system in the co-evolution ofV .cholerae and its phages, presumably fostered by their enhanced interactions during seasonal epidemics of cholera.